CULTURALLY INDEPENDENT VILLAGE AS A COMMUNITY DEVELOPMENT STRATEGY IN GIRIKERTO VILLAGE, SPECIAL REGION OF YOGYAKARTA - Ahdiyana, Marita; Ramadani, Hanifah Tisha (Universitas Negeri Yogyakarta, 2024)
This study examines community development in Girikerto Village through the Desa Mandiri Budaya (Culturally Independent Village) program using a descriptive qualitative approach. The program encourages residents to identify their needs, design solutions, and take action for sustainable change. Government support, mainly through Special Financial Assistance, was important at the start, but the program has gradually promoted community independence. The four supporting pillars of the program involve strong participation from local residents. Community members manage the Bodronoyo Tourism Community Group, Gerbang Merapi Village-Owned Enterprise, and the Water Tank Filling Station. However, the involvement of the younger generation remains unclear. Local entrepreneurship is a key driver of development. Girikerto utilizes its potentials, including tourism, Micro, Small, and Medium Enterprises, animal husbandry, Etawa goat milk processing, and the use of natural and water resources. The Water Tank Filling Station notably contributes to Village Own-Source Revenue, supporting financial independence and the sustainability of the program. Overall, the study shows how external support can evolve into community-driven efforts, helping Girikerto build resilience and achieve sustainable local development.